Breast conservation: Is the survival better for mastectomy?. Issue 1 (21st May 2014) - Hwang, E. Shelley; Rubio, Isabel T.; Dixon, J. Michael
<x xml:space="preserve">Abstract</x> Breast conserving therapy with radiation is now firmly established as an effective treatment option for early stage disease, and has been thought for decades to yield equivalent survival outcomes to mastectomy. However, recently published observational studies as well as meta‐analyses suggest not only a locoregional, but possibly a systemic benefit to BCT. Choice of surgery and radiation is only one of numerous factors impacting survival following surgery for early stage breast cancer; competing comorbidities and risk of treatment related side effects from radiotherapy must also be considered in order to make optimal treatment recommendations. J. Surg. Oncol. 2014 110:58–61. © 2014 Wiley Periodicals, Inc.